Odpowiedzi

2010-03-25T19:28:24+01:00
X+2x=x+9
3x-x=9
2x=9
x = 4 i1/2

y+2y-5=11-y
3y+y=11+5
4y=16 / :4
y=4

3a+4=a-1+a+7
3a-a-a=-1+7-4
a=2

10-2b+6-b=10-b+4-b
-2b-b+b+b=10+4-6-10
-b=-2 / : - 1
b=2
2 5 2
Najlepsza Odpowiedź!
2010-03-25T19:30:12+01:00
X+2x=x+9
3x=x+9
3x - x = 9
2x = 9
x = 4.5

y+2y-5=11-y
3y - 5 = 11 - y
3 y + y = 11 + 5
4 y = 16
y = 4

3a+4=a-1+a+7
3a+4=2a + 6
a = 6-4
a = 2


10-2b+6-b=10-b+4-b
-2b-b+b+b=10+4-10-6
-b=-2
b=2
1 5 1
2010-03-25T19:40:33+01:00
X + 2x = x + 9
3x = x +9
2x = 9 | :2
x = 4,5

y + 2y - 5 = 11 - y
3y - 5 = 11 - y
3y - y = 11 +5
2y = 16 | :2
y = 8

3a + 4 = a - 1 + a +7
3a - a - a = 1 + 7 - 4
a = 4

10 - 2b + 6 - b = 10 - b + 4 - b
4 - 2b - b =10 - b + 4 - b
4 - b = 10 - b + 4 -b
4 - b = 6 - b - b
- b + b - b = 6 - 4
b = 2
2 4 2